Citrus Flavonoids as Promising Phytochemicals Targeting Diabetes and Related Complications: A Systematic Review of In Vitro and In Vivo Studies - Gandhi, Gopalsamy Rajiv; Vasconcelos, Alan Bruno Silva; Wu, Ding-Tao; Li, Hua-Bin; Antony, Poovathumkal James; Li, Hang; Geng, Fang; Gurgel, Ricardo Queiroz; Narain, Narendra; Gan, Ren-You (Nutrients, 2020)
The consumption of plant-based food is important for health promotion, especially concerning the prevention and management of chronic diseases. Flavonoids are the main bioactive compounds in citrus fruits, with multiple beneficial effects, especially antidiabetic effects. We systematically review the potential antidiabetic action and molecular mechanisms of citrus flavonoids based on in vitro and in vivo studies. A search of the PubMed, EMBASE, Scopus, and Web of Science Core Collection databases for articles published since 2010 was carried out using the keywords citrus, flavonoid, and diabetes. All articles identified were analyzed, and data were extracted using a standardized form. The search identified 38 articles, which reported that 19 citrus flavonoids, including 8-prenylnaringenin, cosmosiin, didymin, diosmin, hesperetin, hesperidin, isosiennsetin, naringenin, naringin, neohesperidin, nobiletin, poncirin, quercetin, rhoifolin, rutin, sineesytin, sudachitin, tangeretin, and xanthohumol, have antidiabetic potential. These flavonoids regulated biomarkers of glycemic control, lipid profiles, renal function, hepatic enzymes, and antioxidant enzymes, and modulated signaling pathways related to glucose uptake and insulin sensitivity that are involved in the pathogenesis of diabetes and its related complications. Citrus flavonoids, therefore, are promising antidiabetic candidates, while their antidiabetic effects remain to be verified in forthcoming human studies.